2020
DOI: 10.1103/physrevresearch.2.033459
|View full text |Cite
|
Sign up to set email alerts
|

Valence-bond solids, vestigial order, and emergent SO(5) symmetry in a two-dimensional quantum magnet

Abstract: We introduce a quantum spin-1/2 model with many-body correlated Heisenberg-type interactions on the two-dimensional square lattice, designed so that the system can host a fourfold degenerate plaquette valencebond solid (PVBS) ground state that spontaneously breaks Z 4 symmetry. The system is sign-problem free and amenable to large-scale quantum Monte Carlo simulations, thus allowing us to carry out a detailed study of the quantum phase transition between the standard Néel antiferromagnetic (AFM) and PVBS state… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 129 publications
(280 reference statements)
1
27
0
Order By: Relevance
“…In some variants of the J-Q model, clearly first-order transitions were observed [5,60,61]. The "checker-board" J-Q (CBJQ) model [5] (and a closely related loop model [62]) has a Z 2 breaking PS phase like that in the SS model.…”
mentioning
confidence: 99%
“…In some variants of the J-Q model, clearly first-order transitions were observed [5,60,61]. The "checker-board" J-Q (CBJQ) model [5] (and a closely related loop model [62]) has a Z 2 breaking PS phase like that in the SS model.…”
mentioning
confidence: 99%
“…It is therefore natural to correlate the high-energy continuum, which we interpret as made of fractionalized magnetic excitations, to the strong J c which in this material cannot be regarded as a small perturbation. The presence of spinons in the spectrum of the Heisenberg AF with strong multi-spin couplings (of which the ring exchange is an example) has been predicted some years ago and is now well established [20][21][22]32]. Interestingly, a recent exact diagonalization study [57] performed on the EHM Hamiltonian has shown that, at J c /J ≈ 1 the excitation spectrum at ( 1 /2, 0) breaks into a continuum of states very close in energy, similarly to what has been calculated for Neél-RVB and Neél-VBS transitions [20,[28][29][30][31].…”
Section: Discussionmentioning
confidence: 97%
“…square lattices have been predicted in several Heisenberglike Hamiltonians [11,19,20,22,[28][29][30]32] spinon pairs have been often invoked to explain the anomalous highenergy dynamics of cuprates [10] and isostructural iridates [12]. However, an undisputed experimental evidence of their existence in 2D is still missing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We argue that, remarkably, these two regimes are separated by a deconfined quantum critical point (DQCP), which we will support through numerics and field theory arguments. In fact, its universality is that of the SO(5) DQCP, which has been studied before [2,[60][61][62][63][64][65][66][67][68][69][70], e.g., as a direct transition between an SO(3) Néel state (the analogue of the blue shaded region in Fig. 2) and a 6), perturbed by a trivial paramagnet (horizontal direction) and a same-sublattice Ising coupling (vertical direction).…”
Section: Introduction 1 II Numerical Studymentioning
confidence: 99%